Prediksi Aliran Permukaan Menggunakan Modifikasi Model Bilangan Kurva - Putu Sudira; Tri Purwadi; Sukresno Sukresno; Meli Nurlaili (agriTECH, 2005)
The objectives of the study are (i) to predict surface runoff of watersheds using modification of curve number model, and (ii) to find out the good fit of model application at different size of watersheds. The research was conducted in Padas sub watershed (3356.48 ha)- and Goseng sub watershed (596 ha), upper Solo watershed, Central Java. The data used for analysis were daily rainfall, daily of water level in the stream, soil type, landuse, and minimum infiltration rate from 1998 up to 2002. Surface runoff was calculated using modification of Soil Conservation Service Curve Number Model, which was integrated with the model of SWRRB (Simulator for Water Resources in Rural Basins). The use of curve number model was based on the availability of data such as soil type evaluation, landuse, conservation practices, initial soil moisture contents, and the hydrologic condition of the watersheds. Results indicated that the model was not valid for bigger watershed (Padas sub watershed). This was denoted by low values of correlation coefficient between observed and predicted surface runoff The tws, indicated that observed and predicted surface runoff are significantly different. On the other hand, for the smaller one (Goseng sub watershed) the model was agreed, it was illustrated by no significantly different between observed and predicted surface runoff based on the statistical measures above.